The Routledge handbook of cultural landscape heritage in the Asia-Pacific
1 online resource.
Keywords: "The Routledge Handbook of Cultural Landscape Heritage in the Asia-Pacific revisits the use, growth, and potential of the cultural landscape methodology in the conservation and management of culture-nature heritage in the Asia-Pacific region. Taking both a retrospective and prospective view of the management of cultural heritage in the region, this volume argues that the plurality and complexity of heritage in the region cannot be comprehensively understood and effectively managed without a broader conceptual framework like the cultural landscape approach. The book also demonstrates that such an approach facilitates the development of a flexible strategy for heritage conservation. Acknowledging the effects of rapid socio-economic development, globalization and climate change, contributors examine the pressure these issues place on the sustenance of cultural heritage. Including chapters from more than 20 countries across the Asia-Pacific region, the volume reviews the effectiveness of theoretical and practical potentials afforded by the cultural landscape approach and examines how they have been utilized in the Asia-Pacific context for the last three decades. The Routledge Handbook of Cultural Landscape Heritage in the Asia-Pacific provides a comprehensive analysis of the processes of cultural landscape heritage conservation and management. As a result, it will be of interest to academics, students and professionals who are based in the fields of cultural heritage management"--